Antecedents of halal food consumer behaviour in Malang: The mediating effect of purchase intention - Evina Nahdiya Sani; Syafrial Syafrial; Dwi Retno Andriani (Jurnal Ekonomi dan Keuangan Islam, 2025)
Purpose – The purpose of this research is to examine the factors that influence consumers’ purchase behavior for halal food. Additionally, this research aims to determine the influence of purchase intention mediation on purchasing decisions made at Chinese food restaurants in Malang. Methodology – This study employed a non-probability sampling method, specifically the purposive sampling technique. A total of 344 samples. The collected data were then analyzed using structural equation modeling partial least squares (SEM-PLS). Findings – The research findings indicate that attitudes, halal certification, and food safety exert a positive influence on purchase intention. In contrast, factors such as subjective norms, perceived behavioral control, and halal awareness did not have a significant impact. A positive attitude toward halal products, halal certification, and food safety has been shown to increase purchase intention, thereby influencing purchase decisions. However, this study reveals that purchase intention mediates only a part of the variables. Implications – The expanding halal food industry necessitates a heightened focus on consumer behavior by business actors. These findings suggest that companies can devise more efficacious marketing strategies by accentuating positive consumer attitudes toward halal products and ensuring the presence of valid halal certification and guaranteed food safety standards. Originality – This research proposes an extension to the theory of planned behavior, incorporating three novel variables: halal awareness, halal certification, and food safety. Furthermore, this research focuses on Chinese food restaurants that offer halal food in Malang.